PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS KONSUMEN PADA CAFE D‘PUNCAK DI SAMARINDA - Heriyanto Heriyanto (Prodi Ilmu Administrasi Negara, 2015)
The problem of this study is whether the quality of service which consists of reliability, responsiveness, assurance, empathy, and physical evidence of a significant effect on customer loyalty, and of the five variables examined which has the most dominant and significant influence on customer loyalty at Cafe D 'Puncak in Samarinda.Marketing management is the analysis, planning, implementation and monitoring of programs aimed at causing exchanges with target markets with a view to achieving the company's goals. The first hypothesis of this study is the quality of service which consists of reliability, responsiveness, assurance, empathy, and physical evidence of a significant effect on customer loyalty at Cafe D'Puncak in Samarinda and the second hypothesis is the reliability (reability) has the most dominant influence and significant customer loyalty at Cafe D'Puncak in Samarinda. The population of this study is that consumers Cafe D'Puncak, while the sample is the smallest part of the population that is considered representative or may represent respondents overall. In this study, researchers took 50 samples. The sampling technique using nonprobability sampling that the incidental technique. Where sampling by coincidence, that anyone who by chance met with researchers can be used as a sample if the person who happened to be found are considered suitable as a source of data. The data that has been collected in an analysis using multiple linear regression. The formula used to calculate the linear regression is: Y = a + b1x1 + b2X2 + b3X3 + b4X4 + b5X5 + e. The author using SPSS. Based on the analysis and discussion, showed that the quality of services such as reliability, responsiveness, assurance, empathy, and physical evidence of a significant effect on customer loyalty. These findings support the first hypothesis. Variables are dominant and significant effect is variable physical evidence. These findings reject both hypotheses.